Seasonal Variations in the Sources and Influential Factors of Aerosol Dissolved Black Carbon at a Southeast Coastal Site in China. Issue 7 (6th April 2023) - Zhang, Ruoyang; Qiao, Jing; Huang, Dekun; Lin, Xihuang; Tian, Li; Wang, Baiyun; Bao, Hongyan; Kao, Shuh‐Ji
Abstract: Aerosols are a significant source of dissolved black carbon (DBC) in the ocean. However, how anthropogenic activities, including fossil fuel (FF) burning and human‐initiated biomass burning (BB), would affect the seasonal variations in the concentration and condensation degree of aerosol DBC was not well constrained. To fill this knowledge gap, we collected 33 aerosol samples from December 2018 to September 2019 at a southeast coastal site in China. Concentrations of DBC, water‐soluble organic carbon (WSOC), and elemental carbon (EC) were determined, and air quality data were collected. DBC concentration was 0.02–0.23 μgC m −3, with significantly higher values in spring and winter, and was affected by sources, rainfall frequency, and secondary processes. The source of DBC, as indicated by DBC/WSOC (range: 0.009–0.045) and DBC/EC (range: 0.007–0.065), was dominated by FF burning. Furthermore, the significantly higher DBC/WSOC value in late April to July indicated enhanced contribution from BB that was mainly associated with airmass transported from Southeast Asia (SEA). We further estimated that ∼30% of aerosol DBC was from BB from May to July. The condensation degree of DBC was variable, with significantly higher values in winter and spring, which might be associated with prolonged photo‐dissolution. Significant correlations were also observed between DBC and PM10 and PM2.5, which might be utilized to estimate DBC deposition flux, albeit requiring more studies. Our study emphasized the influence of human activities (including BB activities) on atmospheric DBC deposition, which might affect the regional and even global DBC pools. Plain Language Summary: As a significant source of dissolved black carbon (DBC) to the ocean, the sources and temporal variation in its concentration and condensation degree were not well constrained. In this study, we collected 33 aerosol samples at a coastal site in China. We determined concentrations of DBC, water‐soluble organic carbon, and elemental carbon (EC). Air quality and meteorological parameters were also collected. Our results showed that DBC at this coastal site was primarily derived from fossil fuel (FF) burning, with enhanced contribution from biomass burning that was brought by East Asian Monsoon. In addition, DBC concentration varied significantly among seasons, and was influenced by changes in sources, rainfall frequency as well as secondary processes. Moreover, we found that DBC concentration was significantly positively correlated with PM10 and PM2.5, which provided a potential way to predict DBC depositional flux in other regions that was mainly affected by FF burning. Our study indicated that human activities (FF burning and human‐initiated biomass burning) could have significant impact on atmospheric DBC deposition, which might also affect the oceanic DBC pool in the future. Key Points: The seasonal variation in the dissolved black carbon (DBC) concentration was affected by sources, rainfall frequency, and secondary processes in Xiamen The sources of DBC in the aerosols mainly originated from the burning of fossil fuel The DBC concentration was highly significantly correlated with PM10 and PM2.5, which could be a simple way to estimate DBC deposition flux